Impact of the membership in the European Union on economic growth in Poland - Danuta Hübner (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
Unification of Europe through development and enlargement of the European Union is a great political success. Poland is also joining the EU hoping to accelerate development. Although this enlargement signifies new investment opportunities in Europe and it will create the largest internal market world-wide, a market of over 450 million consumers, the economy, remains the greatest challenge to the united Europe. EU accession for Poland, the largest new EU member, might mean faster long-term economic growth. This paper tries to asses the possible impact of Poland's membership in the EU on economic growth. It analyses the development gap between Poland and so called old European Union states. It attempts to estimate the real convergence in the EU. It also analyses the factors determining the speed of real convergence in EU-15 cohesion countries. Eventually it describes guidelines for Polish economic policy ensuing from experiences of cohesion states.
Keywords: 330; Wirtschaftswachstum; EU-Mitgliedschaft; Mitgliedschaft; Wirtschaftliche Konvergenz; Polen; EU-Staaten